2023
DOI: 10.1007/s40489-023-00356-8
|View full text |Cite
|
Sign up to set email alerts
|

“I Always Knew I Was Different”: Experiences of Receiving a Diagnosis of Autistic Spectrum Disorder in Adulthood—a Meta-Ethnographic Systematic Review

Abstract: A broadening of diagnostic criteria and increased awareness of autism has led to a large number of individuals whose difficulties remained undetected until adulthood. This systematic review aimed to synthesise empirical evidence of the experience of individuals who received their diagnosis of autism in adulthood. Eight studies met the inclusion criteria. A meta-ethnographic approach was used to synthesise the findings. Analysis revealed two meta-themes: feeling “like an alien” and the “not guilty” verdict, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
(135 reference statements)
1
3
0
Order By: Relevance
“…For example, Groenman et al found higher levels of menopausal complaints in autistic women aged 40 years and older and Moseley et al (2020 , 2021 ) reported similar struggles with participants reaching a breaking point in menopause. This study also corroborates research related to late-diagnosed autistic females, which indicated a lifetime of struggles in ‘fitting in’ with neurotypical society, followed by discovery of a new autistic identity that allowed for better self-acceptance and understanding ( Gellini & Marczak, 2023 ; Leedham et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…For example, Groenman et al found higher levels of menopausal complaints in autistic women aged 40 years and older and Moseley et al (2020 , 2021 ) reported similar struggles with participants reaching a breaking point in menopause. This study also corroborates research related to late-diagnosed autistic females, which indicated a lifetime of struggles in ‘fitting in’ with neurotypical society, followed by discovery of a new autistic identity that allowed for better self-acceptance and understanding ( Gellini & Marczak, 2023 ; Leedham et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…This may resemble a case of Highly Superior Autobiographical Memory, but it differs from the one reported by Parker et al (2006) as A does not have memories by date and her memories are in the form of sensations. A was diagnosed with autism in 2018, and her narrative aligns with that of other adults who received their autism diagnosis in adulthood (Gellini & Marczak, 2023). Since childhood, A felt lonely, misunderstood, unable to comprehend people.…”
Section: Case Reportmentioning
confidence: 88%
“…Being perceived as “different,” and social isolation, have been noted as vulnerabilities to being bullied in autistic children (Humphrey & Hebron, 2015). Moreover, a review exploring autistic women’s experiences by Gosling et al (2023) found that social difficulties increased their level of vulnerability to sexual exploitation and abuse, including having difficulties judging subtle social cues, reading other people’s intentions, and understanding social rules. In addition, experiences of bullying were attributed to perceived differences such as social interaction, being very intellectual and differing interests (Gosling et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a review exploring autistic women’s experiences by Gosling et al (2023) found that social difficulties increased their level of vulnerability to sexual exploitation and abuse, including having difficulties judging subtle social cues, reading other people’s intentions, and understanding social rules. In addition, experiences of bullying were attributed to perceived differences such as social interaction, being very intellectual and differing interests (Gosling et al, 2023). Furthermore, a perceived lack of communication to report the abuse and lack of social network may lead to being targeted.…”
Section: Discussionmentioning
confidence: 99%